Outcomes of lenalidomide‐ or bortezomib‐based regimens in older patients with plasma cell myeloma. Issue 1 (3rd October 2020) - Barth, Peter; Giri, Smith; Reagan, John L; Olszewski, Adam J
Abstract: The "triplet" regimen of lenalidomide, bortezomib, and dexamethasone (RVD) showed survival advantage over lenalidomide‐dexamethasone (RD) in clinical trials, but older patients with myeloma often receive doublet regimens (RD or bortezomib‐dexamethasone, VD), or VD plus cyclophosphamide (VCD). We compared these first‐line regimens using real‐world data from Medicare beneficiaries receiving therapy between 2007 and 2015. In each comparative analysis, we balanced confounding characteristics using a propensity score. Outcomes included overall (OS) and event‐free survival (EFS, reporting hazard ratios [HR] with 95% confidence intervals [CI]), adverse events, and costs. We identified 6076 patients with median age 76 and median OS of 2.6 years. In the comparison of RVD vs RD/VD doublets, RVD showed significantly better OS (HR = 0.83; 95% CI, 0.72‐0.95) and EFS (HR = 0.68; 95% CI, 0.61‐0.76). So, RVD was associated with more frequent hospitalizations, anemia, and neuropathy, but no increase in thromboembolism or secondary cancers. Costs were higher with RVD. In the comparison of RD vs VD, RD demonstrated better EFS (HR = 0.74; 95% CI, 0.68‐0.81) and marginally better OS (HR = 0.91; 95% CI, 0.83‐0.99). And, RD resulted in significantly more thromboembolic events, less neuropathy, and no significant difference in hospitalizations, transfusions, or secondary cancers. In the comparison of VCD vs VD, we observed no significant difference in any outcome. Superior survival favors RVD over doublet regimens, but even in 2015 RVD was applied for only about 25% of Medicare beneficiaries with myeloma. For patients not eligible for RVD due to toxicity, VCD offers no survival benefit over VD. Lenalidomide‐dexamethasone may be the preferred line doublet considering its advantage over VD.